Meningkatkan Kemampuan Guru dalam Menyusun Perencanaan Pembelajaran Melalui Pembinaan Kolaboratif Bagi Guru Kelas V di Dabin II Unit Pendidikan Kecamatan Gedangan: Improving Teacher Ability in Developing Learning Planning Through Collaborative Coaching for Class V Teachers at Dabin II Education Unit of Gedangan District - Hanifa, Hanifa (Pedagogia : Jurnal Pendidikan, 2017)
The problem in this research is not all teachers make the development of silabus and plan of learning implementation independently. This study aims to improve the willingness and ability of teachers in making the development of silabus and learning implementation plan (RPP) so that the process of teaching and learning directed learning achievement increases. The data source comes from the instrument delivered to all class V teachers in the Gedangan District, especially in the developed areas II. Analisis data is done by using descriptive and qualitative analysis, then consulted with the success criteria to determine whether collaborative coaching can improve the ability and willingness of teachers in making silabus and RPP. Based on the result of observation of silabus in the first cycle in obtaining the data of the percentage increase of conformity that is on the component of the teaching material from 50% to 75%, the learning activity increased from 25% to 75%, the indicator from 25% to 75%, the assessment type from 50% to 75%. While in the second cycle of RPP preparation there is an increase in terms of determining the existing learning model has increased: from 25% to 75% increase and assessment aspect from 25% to 75% increase, Indicator increased from 25% to 75% learning increased from 50% to 75%, teaching materials from 25% to 75%. Based on the results of data analysis above drawn the conclusion that: Collaborative coaching can improve the ability of teachers in making the development of silabus and learning implementation plan.